(E)-5-[(2-Hydroxy-3-methoxybenzylidene)amino]-1,3,4-thiadiazole-2(3H)-thione - Kargar, Hadi (International Union of Crystallography, 2011)
In the title compound, C(10)H(9)N(3)O(2)S(2), the dihedral angle between the benzene ring and the five-membered ring is 1.54 (13)°. An intramolecular O—H⋯N hydrogen bond makes an S(6) ring. In the crystal, molecules are linked together through bifurcated N—H⋯(O,O) hydrogen bonds having R (1) (2)(5) ring motifs, forming chains along the b axis. The crystal structure also features π–π interactions, with centroid–centroid distances of 3.699 (3)–3.767 (3) Å.